Preparation and Evaluation of Adsorbents from Coal and Irvingia gabonensis Seed Shell for the Removal of Cd(II) and Pb(II) Ions from Aqueous Solutions - Ezeokonkwo, Mercy A.; Ofor, Okechukwu F.; Ani, Julius U. (Frontiers in Chemistry, 2018)
The adsorption of Cd(II) and Pb(II) ions on adsorbents prepared from sub-bituminous coal, lignite and a blend of coal and Irvingia gabonensis seed shells was investigated. Fourier transform infrared, scanning electron microscope and X-ray fluorescence analyses implicated hydroxyl, carbonyl, Al2O3 and SiO2 as being responsible for binding the metal ions on the porous adsorbents. The optimum adsorption of carbonized lignite for the removal of Cd(II) and Pb(II) ions from aqueous media were 80.93% and 87.85%, respectively. Batch adsorption was done by effect of adsorbent dosage, pH, contact time, temperature, particle size, and initial concentration. Equilibrium for the removal of Pb(II) and Cd(II) was established within 100 and 120 min respectively. Blending the lignite-derived adsorbent with Irvingia gabonensis seed shell improved the performance significantly. More improvement was observed on modification of the blend using NaOH and H3PO4. Pb(II) was preferentially adsorbed than Cd(II) in all cases. Adsorption of Cd(II) and Pb(II) ions followed Langmuir isotherm. The kinetics of adsorption was best described by pseudo-second order model. The potential for using a blend of coal and agricultural byproduct (Irvingia gabonensis seed shell) was found to be a viable alternative for removal of toxic heavy metals from aqueous solutions.